Compare the Educational Environment and Prevalence of Myopia in Public and Private Schools : Educational Environment and Prevalence of Myopia - Jabbar, Maryam; Ahmed, Farooq; Rashid, Faisal; Siddiq, Saqib; Bhatti, Muhammad Mueen; Ihsan, Khawaja Mohsin (Pakistan BioMedical Journal, 2025)
Myopia is a major cause of worldwide avoidable blindness, and its prevalence is increasing rapidly. Objectives: To investigate the relationship between myopia and educational environmental characteristics in public and private sectors. Methods: A cross-sectional study was conducted from August to December 2024, implementing a stratified sampling technique. Two schools were chosen at random from each of the public and private school strata. From each grade level, students were then selected at random. Individuals with ocular problems or those who declined to participate were not included. 621 students between the ages of 8 and 15 took part. Ocular examination included refraction and visual acuity. A self-structured questionnaire was utilized to assess the home and school educational environment variables. SPSS version 26.0 was used for data analysis. Results: Among 621 students (mean age 13 ± 1.89 years), 46.53% were male and 53.46% were female. 387 students attend public schools, while 234 attend private. 33.8% myopia prevalence, with 10% having high, 33.33% having moderate and 56.66% having mild myopia. There were 109 myopes from private schools and 101 from public schools. 109 out of 234 students in private schools (46.58%) have myopia. A pleasant study area and the amount of time spent on homework are all factors linked to myopia in public and private school types. Conclusions: It was concluded that a notable difference was found in the public and private sectors’ educational environments. More artificial lighting, fewer outside activities, and a stronger focus on digital learning resources like laptops and tablets are features associated with private schools.